An Analysis of India’s Blooming Gig Workers - Bhattarai, Dambaru (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The present study aimed to analyze the estimated trends and patterns of gig workers in India. It also attempted to analyze the social security and income patterns of the gig workers, along with the several issues and challenges of the gig workers. Methodology : The present study was purely based on secondary data collected from government reports. Using these reports, relevant tables and figures were prepared. The research adopted a descriptive approach. Findings : As per the estimation of 2021, 7.7 million workers were engaged in the gig economy of the country, and it was expected that this number would expand to 23.5 million by 2029–2030. In 2019–2020, 62.4% of the gig workers engaged in the unorganized sector, though their share decreased compared to 2011–2012. A total of 38.7% of the gig workers were medium-skilled, followed by 33.8% who were low-skilled. Most of the gig workers face unstable incomes, insecure jobs, and the worst working conditions. Policy Implications : The study recommended that a proper policy should be designed for poor workers. All gig workers should be registered and provided with an employee identity card, which would enable them to access social security benefits. Additionally, specific working hours should be established for these workers. However, these policies were found to be insufficient to fully address the needs of gig workers. Originality : The present study proposed specific policy recommendations that have not been addressed in the previous papers.